Entrepreneurship, development, and the spatial context: Retrospect and prospect - Peter Nijkamp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
Entrepreneurship has been a topical issue in the business administration literature, but in the past decade a wave of interest can be observed on the role of entrepreneurship in the economic growth literature. This paper aims to highlight the various contributions to the entrepreneurship literature from the perspective of regional economic development. After a broad overview, particular attention is given to the regional action space of entrepreneurs, including their social and spatial network involvement. The paper concludes with a future research agenda.
Keywords: L26; R11; O31; 330; entrepreneurship; regional growth; action space; networks; SME; virtual organization; innovation; Entrepreneurship-Ansatz; Regionale Entwicklung